solve for t if p≠q (t+p)/q – q/p = (t-q)/p + p/q

Question

solve for t if p≠q
(t+p)/q – q/p = (t-q)/p + p/q

in progress 0
Aaliyah 2 weeks 2021-10-04T20:31:39+00:00 1 Answer 0

Answers ( )

    0
    2021-10-04T20:32:54+00:00

    Answer:

    .. q T 0 = (q/p)a (q/p)a − (q/p)T−10 if p ≠ q and qT0 = 1 − T0/a if p = q = 1/2.

    Step-by-step explanation:

    Suppose that there are two different solutions, p and q, in [a, b]. Thus p =g(p) q =g(q) p ≠ q The function g(x) satisfies the hypotheses of the mean-value … that g(p) –g(q) = (p – q) g׳(t) Because g(p) =p and g(q) = q, the left side of Eq. (1-3) may…

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )